Design and Implementation of Single-Phase Boost PFC Converter - Jafar H. Alwash; Turki K. Hassan; Raed F. Abbas (Journal of Engineering, 2023)
In this paper, a single-phase boost type ac-dc converter with power factor correction (PFC) technique is designed and implemented. A current mode control at a constant switching frequency is used as a control strategy for PFC converter. The PFC converter is a single-stage singleswitch boost converter that uses a current shaping technique to reshape the non-sinusoidal input current drawn by the bulky capacitor in the conventional rectifier. This technique should provide an input current with almost free-harmonics, comply with the IEC61000-3-2 limits, and a system operates with near unity power factor. The other function of the boost converter that should be accomplished is to provide a regulated DC output voltage. The complete designed system is simulated in MATLAB/SIMULINK and a hardware prototype has been built using analog devices. Simulation results and experimental results are presented to validate the proposed system.